Thienothiophene and triphenylbenzene based electroactive conjugated porous polymer for oxygen reduction reaction (ORR) - EROĞLU, MEHMET SAYIP (My University, 2022)
© 2022 The Authors. Published by American Chemical Society.Catalysts based on metal-free conjugated porous polymers (CPPs) are still rare for electrochemical oxygen reduction reactions (ORR). In this study, a conjugated porous polymer, TT-TPB, based on thieno[3,2-b]thiophene (TT) and triphenylbenzene (TPB), was synthesized applying palladium(0) catalyzed Suzuki coupling reaction and its ORR activity was investigated in alkaline condition. It demonstrated comparable electrocatalytic performance of ≈0.89-0.9 V Eonset vs RHE with the commercially available Pt/C. Density-functional theory (DFT) calculations revealed that TT-TPB featured efficient electrocatalytic active sites derived from volumetric, areal, and O2 adsorbing calculations, which were in line with the experimental results. Moreover, semiconducting and surface properties of TT-TPB were investigated in detail using electrochemical and spectrophotometric techniques. This work shows the potential application of thienothiophene-based metal-free CPP in the electrochemical conversion process.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Kimya Mühendisliği ve Teknolojisi; Kimya; Fizikokimya; Elektrokimya; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Signal Processing; Chemical Engineering and Technology; Chemistry; Physical Chemistry; Electrochemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; MÜHENDİSLİK, KİMYASAL; ENERJİ VE YAKITLAR; ELEKTROKİMYA; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING, CHEMICAL; ENERGY & FUELS; ELECTROCHEMISTRY; MATERIALS SCIENCE, MULTIDISCIPLINARY; Kimya Mühendisliği (çeşitli); Fizik Bilimleri; Enerji Mühendisliği ve Güç Teknolojisi; Malzeme Kimyası; Elektrik ve Elektronik Mühendisliği; Chemical Engineering (miscellaneous); Physical Sciences; Energy Engineering and Power Technology; Materials Chemistry; Electrical and Electronic Engineering; thienothiophene; conjugated porous polymer (CPP); polymeric electrocatalyst; oxygen reduction reaction (ORR); metal-free electrocatalyst; catalyst kinetics; OPTICAL-PROPERTIES; NETWORKS; SULFUR; CARBON; 1,3,5-TRIPHENYLBENZENE; ELECTROCATALYST; DERIVATIVES; CAPACITORS; CATALYSTS; OXIDE; thienothiophene; conjugated porous polymer (CPP); polymeric electrocatalyst; oxygen reduction reaction (ORR); metal-free electrocatalyst; catalyst kinetics